Increasing the reliability and durability of moving joints of V-belt variators of grain harvesters (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
The article describes technological methods and measures to protect the moving joints of V-belt variators of grain harvesters. The study of the effectiveness of the developed coatings and measures to protect movable joints from the harmful effects of fretting corrosion in order to prevent destruction, as well as to reduce the intensity of damage to variator parts and movable joints from corrosion, was analyzed.
Keywords: V-belt variator; coupling; reliability; resource; wear; fretting corrosion; friction; oxidation